1957
DOI: 10.1172/jci103452
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Chlorpromazine upon the Adrenal Cortical Response to Insulin Hypoglycemia in Man1

Abstract: The large number of recent publications concerning the inter-relationships between the central nervous system and the anterior pituitary testifies to the intense interest in this subject (2, 3). Particular attention has been devoted to the effects of hypothalamic stimulation or injury upon pituitary ACTH release and adrenal cortical response. The work of deGroot and Harris (4), Hume and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

1959
1959
1981
1981

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…Analytic methods. Free plasma 17-OH-corticosteroid levels were determined by the Silber-Porter method (25) as modified in this laboratory (26). Plasma workers (20).…”
Section: Methodsmentioning
confidence: 99%
“…Analytic methods. Free plasma 17-OH-corticosteroid levels were determined by the Silber-Porter method (25) as modified in this laboratory (26). Plasma workers (20).…”
Section: Methodsmentioning
confidence: 99%
“…The hypoglycemic state is combated by the counterregulatory release of epinephrine (23), adrenocorticosteroids (24), and glucagon (25). Epinephrine and cortisol strongly inhibit the enhancing effect of insulin on glucose uptake by rat diaphragm (26,27), wherefore their presence in excess in test plasmas could have blunted the full betacytotropic effects of sulfonylurea agents.…”
Section: Comparison Of Insulagenic Potenciesmentioning
confidence: 99%
“…G-s Cristy et al 15 reported a diminished adrenoeortical response to insulin hypoglycaemia in chlorpromazine-treated patients; Gold et al 1~ observed that chlorpromazine decreased the response to injections of metyrapone (su-4885), although the response to operation was unaffected. Sloane et aI.…”
Section: Discussionmentioning
confidence: 99%